Substantive representation of women by parliamentarians in Asia: A comparative study of ten countries - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2022)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book presents the results of a pioneering new large-scale study on how national parliamentarians in Asia are advancing women’s substantive representation and gender equality. It focuses on substantive representation of women (SRW). The book explores how personal backgrounds and experiences of members of parliament (MPs) have shaped their thinking and commitment to advancing SRW and gender equality. It focuses on institutional dimensions of SRW drawing heavily on MP interviewees’ responses while some authors assess the degree to which the parliament is “gender-sensitive”. The book emphasizes how societal attitudes are the most important solution to gender equality, that both critical actors and critical mass are necessary in Asian parliaments, and that those factors inhibiting numerical representation tend to impede substantive representation.